Diabetes mellitus knowledge of type 2 diabetic patients, Almajmaah, Saudi Arabia - Sami, Waqas; Ansari, Tahir; Butt, Nadeem Shafique; Mohd Rashid, Ab Hamid (International Journal of Advanced Life Sciences, 2017)
The aim of our study was to assess the level of knowledge of type 2 Saudi diabetics regarding diabetes and its domains (symptoms and causes,complications, food and exercise, medication, prevention of diabetes, investigations and understanding of diabetes). This cross-sectional study was conducted on type 2 diabetic Saudi patients visiting the Primary Health Care Centers in Almajmaah city. The data comprising 350 patients was collected from 5th February –24th April, 2017 through a systematic sampling technique using the direct investigation method. Data was collected through self – developed validated questionnaire. Type 2 diabetics had overall poor diabetes mellitus knowledge (42.41%, P<0.001) when compared with the threshold value of 50%. Moreover, diabetics had poor knowledge in all domains i.e. symptoms and causes (33.33%), complications (47.75%), food and exercise (43.40%), medication (29.75%), prevention of diabetes (30%), investigations (35%) and understanding of diabetes (38%). Based on our findings, interventions are required and patients should be empowered for better self-management of diabetes through educational programmes.